Mindfulness Meditation Reduces Intraocular Pressure, Lowers Stress Biomarkers and Modulates Gene Expression in Glaucoma: A Randomized Controlled Trial. Issue 12 (December 2018) - Dada, Tanuj; Mittal, Deepti; Mohanty, Kuldeep; Faiq, Muneeb A.; Bhat, Muzaffer A.; Yadav, Raj K.; Sihota, Ramanjit; Sidhu, Talvir; Velpandian, Thirumurthy; Kalaivani, Mani; Pandey, Ravindra M.; Gao, Ying; et al.
Abstract : Background: Reducing intraocular pressure (IOP) in primary open-angle glaucoma (POAG) is currently the only approach to prevent further optic nerve head damage. However, other mechanisms such as ischemia, oxidative stress, glutamate excitotoxicity, neurotrophin loss, inflammation/glial activation, and vascular dysregulation are not addressed. Because stress is a key risk factor affecting these mechanisms, we evaluated whether mindfulness-based stress reduction can lower IOP and normalize typical stress biomarkers. Materials and Methods: In a prospective, randomized trial 90 POAG patients (180 eyes; age above 45 y) were assigned to a waitlist control or mindfulness meditation group which practiced daily for 21 days. We measured IOP (primary endpoint), quality of life (QOL), stress-related serum biomarkers [cortisol, β-endorphins, IL6, TNF-α, brain-derived neurotrophic factor (BDNF), reactive oxygen species (ROS), total antioxidant capacity (TAC)], and whole genome expression. Results: Between-group comparisons revealed significantly lowered IOP in meditators (OD: 18.8 to 12.7, OS 19.0 to 13.1 mm Hg) which correlated with significantly lowered stress-biomarker levels including cortisol (497.3 to 392.3 ng/mL), IL6 (2.8 to 1.5 ng/mL), TNF-α (57.1 to 45.4 pg/mL), ROS (1625 to 987 RLU/min/104 neutrophils), and elevated β-endorphins (38.4 to 52.7 pg/mL), BDNF (56.1 to 83.9 ng/mL), and TAC (5.9 to 9.3) (all P <0.001). These changes correlated well with gene expression profiling. Meditators improved in QOL ( P <0.05). Conclusions: A short course of mindfulness-based stress reduction by meditation in POAG, reduces IOP, improves QOL, normalizes stress biomarkers, and positively modifies gene expression. Mindfulness meditation can be recommended as adjunctive therapy for POAG. Abstract : Supplemental Digital Content is available in the text.